1975
DOI: 10.1212/wnl.25.3.294
|View full text |Cite
|
Sign up to set email alerts
|

The thymus gland in elderly patients with myasthenia gravis

Abstract: This study was undertaken to determine the amount and histologic appearance of the persistent thymic tissue removed post mortem from 20 patients over 60 years of age with myasthenia gravis. One patient died several days after thymectomy. No recognizable thymic tissue on gross examination was seen in any patient. On microscopic examination, 11 patients had no thymic tissue. The other nine patients, including the one with thymectomy, all showed marked involution of the thymus. No germinal centers were seen. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
3

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 0 publications
2
16
0
3
Order By: Relevance
“…Our results are comparable to those found in earlier studies [5, 26, 27, 28, 29, 30, 31]. In our opinion, the age at MG onset is a more important factor than the age at thymectomy [7, 23, 32].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are comparable to those found in earlier studies [5, 26, 27, 28, 29, 30, 31]. In our opinion, the age at MG onset is a more important factor than the age at thymectomy [7, 23, 32].…”
Section: Discussionsupporting
confidence: 91%
“…While the concentration of AChR antibodies is highest in early-onset MG [7], the occurrence of titin and RyR antibodies is highest in late-onset MG [23, 33, 34]and is accompanied by a more severe disease in late-onset MG [22, 23, 35, 36]. Histologically, thymic hyperplasia is seen in thymuses from early-onset MG patients, while thymuses from late-onset MG patients are atrophic [28, 37, 38, 39]. There is a correlation between thymic hyperplasia and DR3, while the presence of titin antibodies in nonthymoma MG patients has been reported to correlate with DR7 [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…O índice de remissão entre os nossos pacientes de 48% é comparável aos índices relatados na literatura que variam de 8,3% a 54% 3,13,16,18,19,20,22 .…”
Section: Comentáriosunclassified
“…Não indicamos timectomia para miastênicos sem timoma com mais de 50 anos porque o timo nos idosos não contém tecido tímico ou apresenta involução acentuada 20 . Todavia, vários autores 2,7,15,23 não acham que idade seja contraindicação para timectomia.…”
Section: Comentáriosunclassified
“…Such follicles are infrequent in normal adults but do occur in some patients with SLE or thyrotoxicosis. Perlo et al [145] suggested that hyperplasia does not occur in the elderly MG patient but others [117] report its occurrence. Thymomas occur in 10-157o of MG patients [22,101].…”
Section: Clinical Manifestationsmentioning
confidence: 99%